Development and use of influenza vaccines - Tyrrell, D. A. J. (1981)
The development and use of effective influenza vaccines remains an important aspect of attempts to control the disease. Most influenza vaccination programmes use inactivated vaccines, but attenuated live vaccines are used in several countries. Studies comparing the relative efficacies of live and inactivated vaccines are needed. Three types of inactivated vaccine are in routine use: whole virus vaccine (WVV), disrupted virus vaccine (DVV), and surface antigen vaccine (SAV). Further studies should be encouraged to confirm both the overall efficacy of annual revaccination of population groups in the interpandemic period, and the ability of inactivated vaccines to prevent mortality in the aged and other high-risk groups. In the meantime it is important to exploit recent improvements in the knowledge of the chemical and antigenic structure of influenza viruses and modern techniques of molecular biology to develop vaccines of improved design and efficacy. Live attenuated vaccines offer potentially important means for the prevention and control of influenza in all age groups. Laboratory and clinical studies have involved mainly three types of attenuated vaccine strain: (i) wild viruses that have been attenuated by the transfer of genes from host-range-mutant parent strains, which have themselves had extensive laboratory passage and have been shown to be fully attenuated for man; (ii) temperature sensitive (ts) strains, which possess defined ts lesions induced by chemical mutagens, and (iii) cold-adapted strains, i.e., viruses that, after extensive serial passage at low temperatures, grow well at 25° C and not at 37° C. There is evidence that live vaccine strains based on a cold-adapted parent are fully attenuated, immunogenic, and in preliminary tests, do not spread even between children. Research should continue into the identification of suitable, well characterized, safe, and effective parent viruses which may be used as reliable donors of genes associated with attenuation. Vaccine strains should possess stable genetic markers to facilitate identification of the vaccine virus for epidemiological purposes.